Depression in the Mirror: Depression Severity and Its Link to Negative Judgments of Symptoms - Visco-Comandini, Federica; Gragnani, Andrea; Giacomantonio, Mauro; Romano, Giuseppe; Petrucci, Manuel; Mancini, Francesco (Frontiers in Psychiatry, 2021)
Background and objectives: Depressive states represent a normal and physiological response to the experience of loss. However, it is possible to identify some elements that allow distinguishing physiological depressive states from pathological ones. Over the years, research has confirmed that a stable tendency to negative self-evaluation is a transdiagnostic factor that triggers and amplifies dysfunctional emotional reactivity, thus contributing to the shift from normal to pathological reaction. In this sense, the secondary problem, or meta-emotional problem, referring to the negative evaluation of one's depressive state and the consequent dysfunctional attempts to solve it, seems to play an important role. The aim of the present study is to investigate how dysfunctional beliefs and the evaluations of depressive symptoms (meta-emotional problems) are related to depression severity. Methods: we asked to a community sample to focus on the depressive symptoms they regard as most distressful and evaluate them through specific questionnaires. 189 participants were asked to complete a set of questionnaires: (1) the Meta-Emotional Problem Questionnaire; (2) the Center for Epidemiologic Studies Depression Scale; (3) the Beck Depression Inventory; (4) the Dysfunctional Attitude Scale-24 in order to investigate the relation between dysfunctional beliefs, meta-emotional problems and depressive symptoms severity. Results: our results show that higher levels of depression are associated both to more pervasive dysfunctional attitudes and increased evaluation of meta-emotional problem. In addition, we conduct a regression analysis to disentangle the impact of the two different measures of depressive symptoms (i.e., BDI-II and CES-D) with two explanatory variables (dysfunctional attitudes and meta-emotional problem). Results show that meta-emotional problem remains a significant and robust predictor of the severity of depressive symptomatology, while dysfunctional beliefs has a rather weak and non-significant relation with the criterion. In other words, meta-emotional problem consistently explains the higher variance of depressive symptoms than dysfunctional beliefs. In conclusion, our study shows a clear link between meta-emotional problem and depression severity. This is relevant for clinical practice, as it highlights the importance of specifically targeting beliefs about the depressive condition in cognitive-behavioral treatment of depression, since they represent crucial factors maintaining depressive symptomatologies.